The Influences of Computer System Success and Informatics Competencies on Organizational Impact in Nursing Environments. - Hsien-Cheng Lin; Meng-Hsiang Hsu; Chen-Wei Yang (CIN: Computers, Informatics, Nursing, 2014)
The previous literature provides evidence that the characteristics of a successful computer system and the informatics competencies of individuals play a critical role in the adoption of information technology. However, while the combined effects of the two may provide a comprehensive view in understanding nursing informatics research, they have rarely been studied simultaneously. Therefore, this study aimed to examine the influences of computer system success and informatics competencies on nursing organizational impact. We surveyed 454 nurses who worked at international patient centers in Taiwan. The results show that both nurses' informatics competencies and nursing computer system success do have influence on nursing organizational impact. Moreover, nurses' informatics competencies have a greater effect than the superior characteristics of a nursing computer system on nursingorganizational performance. Finally, implications for practitioners complete this study.